Macroeconomic Variables and Sukuk Outstanding in Indonesia - Asri, Nur Habibah; Dwi Wulandari (HM Publisher, 2021)
Sukuk or Sharia bonds are one of the investment instruments in Indonesia. Since the 19th century, Sukuk has become popular with investors. Several previous studies found contradictory results that macroeconomic variables have a relationship and influence on Sukuk by observing the year before the pandemic. This study uses a quantitative descriptive method with a Vector Autoregression (VAR) approach. Through the optimum lag value, namely, lag 3, statistically it was found that there was a significant relationship between the variables of GDP, interest rates, and the exchange rate on Sukuk. In addition, several analysis results found a causal relationship between these variables.